HUGO CHÁVEZ: POPULISM WITH UNIFORM - Arenas, Nelly (2018)
This article discusses the historical development of Hugo Chavez’s Bolivarian Revolution from its origins in the early 1980s until the death of the leader in March 2013. Emphasis is given to those aspects that allow a better understanding of the nature of the populist chavista regime such as militarism that distinguishes it; its nationalism; its participatory character; the content of the 21st century socialism, among others.